A new cave-dwelling species of the genus Mesoiulus Berlese, 1886 (Diplopoda, Julida, Julidae) from Turkey - Antić, Dragan Ž.; Çetin, Cemal Çağri; Turantepe, Ergin; Gürbüz, Mehmet Faruk (Zootaxa, 2016)
A new cave-dwelling species of the poorly defined genus Mesoiulus Berlese, 1886, M. taurus sp. nov., is described from the Zindan Cave, Isparta, Western Taurides, Turkey. A brief discussion of the relationship between M. taurus sp. nov. and the most similar species (M. ciliciensis Strasser, 1975) is presented, as well as a map showing the distribution of the genus Mesoiulus in Turkey.